Oxidative Stress-Induced STIM2 Cysteine Modifications Suppress Store-Operated Calcium Entry - Gibhardt, Christine Silvia; Cappello, Sabrina; Bhardwaj, Rajesh; Schober, Romana; Kirsch, Sonja; Bonilla del Rio, Zuriñe; Gahbauer, Stefan; Bochicchio, Anna; Sumanska, Magdalena; Ickes, Christian; Stejerean-Todoran, Ioana; Mitkovski, Miso; et al. (Cell Reports, 2020)
Store-operated calcium entry (SOCE) through STIM-gated ORAI channels governs vital cellular functions. In this context, SOCE controls cellular redox signaling and is itself regulated by redox modifications. However, the molecular mechanisms underlying this calcium-redox interplay and the functional outcomes are not fully understood. Here, we examine the role of STIM2 in SOCE redox regulation. Redox proteomics identify cysteine 313 as the main redox sensor of STIM2 in vitro and in vivo. Oxidative stress suppresses SOCE and calcium currents in cells overexpressing STIM2 and ORAI1, an effect that is abolished by mutation of cysteine 313. FLIM and FRET microscopy, together with MD simulations, indicate that oxidative modifications of cysteine 313 alter STIM2 activation dynamics and thereby hinder STIM2-mediated gating of ORAI1. In summary, this study establishes STIM2-controlled redox regulation of SOCE as a mechanism that affects several calcium-regulated physiological processes, as well as stress-induced pathologies.
CRIS-Team Scopus Importer:2020-10-30
Keywords: calcium; cysteine; I; melanoma; ORAI; redox; ROS; SOCE; STIM2; thiol